Oxidative Alteration of Ferrous Smectites and Implications for the Redox Evolution of Early Mars. Issue 12 (4th December 2017) - Chemtob, Steven M.; Nickerson, Ryan D.; Morris, Richard V.; Agresti, David G.; Catalano, Jeffrey G.
Abstract: Surface conditions on early Mars were likely anoxic, similar to early Earth, but the timing of the evolution to oxic conditions characteristic of contemporary Mars is unresolved. Ferrous trioctahedral smectites are the thermodynamically predicted products of anoxic basalt weathering, but orbital analyses of Noachian‐aged terrains find primarily Fe 3+ ‐bearing clay minerals. Rover‐based detection of Fe 2+ ‐bearing trioctahedral smectites at Gale Crater suggests that ferrous smectites are the unoxidized progenitors of orbitally detected ferric smectites. To assess this pathway, we conducted ambient‐temperature oxidative alteration experiments on four synthetic ferrous smectites having molar Fe/(Mg + Fe) from 1.00 to 0.33. Smectite suspension in air‐saturated solutions produced incomplete oxidation (24–38% Fe 3+ /ΣFe). Additional smectite oxidation occurred upon reexposure to air‐saturated solutions after anoxic hydrothermal recrystallization, which accelerated cation and charge redistribution in the octahedral sheet. Oxidation was accompanied by contraction of the octahedral sheet (d(060) decreased from 1.53–1.56 Å to 1.52 Å), consistent with a shift toward dioctahedral structure. Ferrous smectite oxidation by aqueous hydrogen peroxide solutions resulted in nearly complete Fe 2+ oxidation but also led to partial Fe 3+ ejection from the structure, producing nanoparticulate hematite. Reflectance spectra of oxidized smectites were characterized by (Fe 3+, Mg)2 ‐OH bands at 2.28–2.30 μm, consistent with oxidative formation of dioctahedral nontronite. Accordingly, ferrous smectites are plausible precursors to observed ferric smectites on Mars, and their presence in late‐Noachian sedimentary units suggests that anoxic conditions may have persisted on Mars beyond the Noachian. Key Points: Oxidation of trioctahedral ferrous smectites by aqueous O2 or H2 O2 produces dioctahedral ferric smectites and Fe oxides or oxyhydroxides Oxidation produces systematic changes in VNIR reflectance spectra of ferrous iron‐bearing smectites Orbitally detected Martian nontronite may be the product of oxidation of ferrous smectite precursors